Layered Silicon‐Based Nanosheets as Electrode for 4 V High‐Performance Supercapacitor. (20th May 2020) - Gao, Runsheng; Tang, Jie; Yu, Xiaoliang; Lin, Shiqi; Zhang, Kun; Qin, Lu‐Chang
Abstract: Silicon‐based materials have shown great potential and been widely studied in various fields. Unlike its unparalleled theoretical capacity as anodes for batteries, few investigations have been reported on silicon‐based materials for applications in supercapacitors. Here, an electrode composed of layered silicon‐based nanosheets, obtained through oxidation and exfoliation, for a supercapacitor operated up to 4 V is reported. These silicon‐based nanosheets show an areal specific capacitance of 4.43 mF cm −2 at 10 mV s −1 while still retaining a specific capacitance of 834 µF cm −2 even at an ultrahigh scan rate of 50 000 mV s −1 . The volumetric energy and power density of the supercapacitor are 7.65 mWh cm −3 and 9312 mW cm −3, respectively, and the electrode can operate for 12000 cycles in a potential window of 4 V at 2 A g −1, while retaining 90.6% capacitance. These results indicate that the silicon‐based nanosheets can be a competitive candidate as the supercapacitor electrode material. Abstract : 2D Si‐based nanosheets (TSNs) are prepared as the electrode material for supercapacitors with an operating voltage up to 4 V. Electrochemical measurements demonstrate that the TSNs electrode has an excellent energy/power density ratio and is advantageous over those of many of the reported Si‐based and 2D materials for supercapacitor applications.